On Dwell Time Minimization for Switched Delay Systems: Free-Weighting Matrices Method - Koru, Ahmet Taha; Delibasi, Akin; Ozbay, Hitay (IEEE, 2014)
In this paper, we present a quasi-convex minimization method to calculate an upper bound of dwell-time for stability of switched delay systems. Piecewise Lyapunov-Krasovskii functionals are introduced and the upper bound for the derivative of Lyapunov functionals are estimated by free weighting matrices method to investigate non-switching stability of each candidate subsystems. Then, a sufficient condition for dwell-time is derived to guarantee the asymptotic stability of the switched delay system. Once these conditions are represented by a set of linear matrix inequalities (LMIs), dwell time optimization problem can be formulated as a standard quasi-convex optimization problem. Numerical examples are given to illustrate improvements over previously obtained dwell-time bounds.
Keywords: Time delay systems; dwell time optimization; switched systems; free weighting matrices method; LINEAR-SYSTEMS; STABILITY; STABILIZATION; Automation & Control Systems